2019
DOI: 10.1073/pnas.1819415116
|View full text |Cite
|
Sign up to set email alerts
|

Programmable microencapsulation for enhanced mesenchymal stem cell persistence and immunomodulation

Abstract: Mesenchymal stem cell (MSC) therapies demonstrate particular promise in ameliorating diseases of immune dysregulation but are hampered by short in vivo cell persistence and inconsistencies in phenotype. Here, we demonstrate that biomaterial encapsulation into alginate using a microfluidic device could substantially increase in vivo MSC persistence after intravenous (i.v.) injection. A combination of cell cluster formation and subsequent cross-linking with polylysine led to an increase in injected MSC half-life… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
110
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 154 publications
(113 citation statements)
references
References 42 publications
3
110
0
Order By: Relevance
“…This limits the MSC's ability to deliver therapeutic payloads to the host environment via secreted paracrine factors to a short period of time following injection (106,108) and limits cell homing to target tissues (i.e., bone marrow and nervous system). Entrapment of MSCs in the lung capillaries also increases susceptibility to immune clearance (83,108). For example, clinical studies on intravenous administration of radiolabeled MSCs for MI showed a complete lack of MSC homing in the infarcted myocardium following intravascular injection (92,109).…”
Section: Insufficient Residence Time and Homingmentioning
confidence: 99%
See 1 more Smart Citation
“…This limits the MSC's ability to deliver therapeutic payloads to the host environment via secreted paracrine factors to a short period of time following injection (106,108) and limits cell homing to target tissues (i.e., bone marrow and nervous system). Entrapment of MSCs in the lung capillaries also increases susceptibility to immune clearance (83,108). For example, clinical studies on intravenous administration of radiolabeled MSCs for MI showed a complete lack of MSC homing in the infarcted myocardium following intravascular injection (92,109).…”
Section: Insufficient Residence Time and Homingmentioning
confidence: 99%
“…These results indicate that controlling the cell number inside microgels is an important consideration to achieve the desired residence time of MSCs. Moreover, this improved in vivo residence time of APA-treated MSCs occurred despite the presence of innate and adaptive immune clearance mechanisms, leading to a significant improvement of therapeutic outcome in a bone marrow transplant model (108).…”
Section: Strategies To Improve Systemic Administrationmentioning
confidence: 99%
“…Preconditioning with cytokines such as IFN-γ or TNF-α enhances immunomodulatory factor secretion by MSCs, but such effects have been reported as temporary [69,290]. Alternative tissue engineering approaches including three-dimensional culture and hydrogel encapsulation were employed to enhance MSC functions [291,292]. The therapeutic potentials of MSCs are attributed to complex cellular and molecular mechanisms of action, and such mechanisms still require in-depth exploration for clinical application.…”
Section: Challenges In Msc-based Therapymentioning
confidence: 99%
“…In some cases, repeated injections over the healing period are required. [ 53 ] Much in the same manner as biomaterials can aid in the retention and therapeutic potential of MSCs delivered by either local [ 10,54 ] or intravenous means, [ 55 ] the use of biomaterials to deliver EVs has emerged as a promising strategy in regenerative medicine to overcome the low retention rates of bolus injections of EVs. Binding to, or encasing EVs in a biomaterial matrix has been shown to extend their bioavailability following delivery, permit sustained and controlled release, maintain stability of EV cargo, and potentially augment therapeutic potency.…”
Section: Introductionmentioning
confidence: 99%